Youth and Adult Education in the countryside and education policies: achievements from the social movements - Adalberto Penha de Paula; Marina Comerlatto da Rosa (Revista Brasileira de Educação do Campo, 2020)
This paper discusses Rural Education and its relation with the field social movements, from the education reality in a settlement of the Landless Rural Workers’ Movement. Its starting point is the school processes related to the Youth and Adult Education in the countryside, considering the education policies registered in the documents that guide the teaching practices carried out in the routine of the field school. It is based on the conception of education and school for Rural Education and the MST pedagogical practices, that is, pedagogical and philosophical principles that support the fight for land and for the right to education within this field social movement. The study problematizes the documents produced by the Education Secretariat of the State of Paraná, the materials produced by the MST and the academic production on Rural Education and Youth and Adult Education. Finally, the results point out the government’s disregard with the Rural Education and evidences that with the advent of social movements, a strong pro-education movement appeared in Brazil, one which fights for the guarantee of the rights of the peasants, the waters and the forests.